Transformation of aluminium fractions and phosphorus availability in acid soils as the result of microbes and ameliorant addition - Dewi Firnia Hanafi; S Anwar; D A Santosa; B Nugroho; D P T Baskoro (Brawijaya University, 2020)
Soil acidity and problems related to aluminium (Al) toxicity are usually limiting factors for soil use in agriculture. Problems with acid soils can be overcome by liming. Another potential way to overcome problems of acid soils is to utilize young coal enriched with sulfate-reducing bacteria (SRB) or Acidithiobacillus ferrooxidans. The purpose of this study was to assess the utilization of coal enriched with SRB or A. ferrooxidans as an alternative ameliorant to provide transformation of aluminium fractions and phosphorus availability in acid soils. There were two acid soils (Ultisols) studied with differences in the content of exchangeable Al. Al fraction was differentiated into exchangeable Al (Al-exch), crystalline Al (Al-dithionite), non-crystalline Al (Al-o), organic Al bound (Al-p), non-crystalline inorganic Al (Al-po), as low or medium complex with organic matter (Al-Cu), highly stabilized Al complex with organic matter (Al-pCu). The results showed that for acid soils from Jasinga West Java and Lebak Banten, coal or lime ameliorant, microbial A. ferrooxidans or sulfate-reducing bacteria (SRB) and coal or lime ameliorant enriched with A. ferrooxidans or sulfate-reducing bacteria (SRB) significantly affected the value of Al fraction. Coal or lime ameliorant enriched with A. ferrooxidans could reduce the Al fraction content in acid soils. Coal or lime ameliorant enriched with SRB could increase the availability of P in acid soil from Jasinga West Java with the distribution of Al-pCu > Al-dhitionite > Al-po > Al-exch > Al-Cu fraction. Coal or lime ameliorant enriched with SRB could increase the availability of P in acid soil from Lebak Banten with the distribution of Al-pCu > Al-po > Al-dhitionite > Al-Cu> Al-exch